Enhanced oxygen transport in ionomer films on platinum electrodes via a local electric field. Issue 39 (21st September 2022) - Zhang, Yuewen; Fan, Linhao; Wang, Jiaqi; Deng, Hao; Shi, Weiyu; Du, Qing; Hou, Zhongjun; Jiao, Kui
Abstract : The oxygen transport in ionomer films on electrodes is enhanced via local electrical field, which inspires novel electrode designs with low oxygen transport resistance for fuel cells. Abstract : The local electric field affects the morphology of ionomer films on electrodes and thus the transport phenomena in ionomer films. Therefore, tuning the local electric field is a potential way to reduce the O2 transport resistance in the catalyst layers of fuel cells. This is the first study to explore the transport phenomena in ionomer films at the nanoscale under a local electric field. The results show that the Pt electrodes become more hydrophilic, thereby suppressing the dense arrangement of perfluorosulfonic acid (PFSA) chains that highly hinder O2 transport under a local electric field. Moreover, the water molecules become more ordered, and the side chains of PFSA are better stretched due to the presence of the electric field. Furthermore, the agglomeration of both water molecules and PFSA molecules is suppressed by the electric field, forming an effective PFSA–water interface for O2 transport. Therefore, the more uniform distributions of water and PFSA molecules, more hydrophilic electrodes and better stretching of PFSA side chains in a stronger electric field help form more O2 transport paths and thus reduce the O2 transport resistance. These findings are valuable for the fundamental understanding of transport phenomena at electrolyte–electrode interfaces under an electric field and inspire novel electrode designs with low O2 transport resistance for fuel cells by strengthening the local electric field.